The Effect of Company Size, Profitability, Leverage, and Institutional Ownership on the Timeliness of Public Company Financial Reporting - Khusnah, Zakiyah Ma'rifatul; Subroto, Bambang (Basic and Applied Accounting Research Journal, 2024)
This study aims to determine the effect of firm size, profitability, leverage, and institutional ownership on the financial reporting timeliness. The population includes all companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2022, from which 1.156 samples are selected through purposive sampling technique. The secondary data of the companies’ annual reports are analyzed by logistic regression utilizing SPSS 25. The study results exhibit that a company's financial reporting timeliness is determined by larger firm size and/or greater institutional ownership. Whilst, profitability and leverage have no effect on the financial reporting timeliness. The implication of this study reveal that firms with larger size and shares majorly owned by institutional shareholders are likely to be on time in reporting their financial statement to the public. As such, investors should consider making investment decisions on larger companies and/or those with greater institutional ownership.